2017
DOI: 10.1063/1.4973659
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution analysis of dynamics processes in laser-produced Al plasmas based on a collisional radiative model

Abstract: The temporal evolution of extreme ultraviolet emission from a laser-produced aluminum plasma has been experimentally and theoretically investigated. Spectra of highly charged Al ions have been measured by using the temporal-spatially resolved laser-produced plasma emission technique. In order to deeply understand the evolution of plasmas and achieve the purpose of rapid diagnosis, a collisional-radiative model has been resolved in the steady-state and time-dependent cases, respectively. The evolution of rate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Colombant and Tonan [5] used units of cm 3 s −1 for rate coefficients for the three dominant processes and to express photoionization rates in these units Su et al considered rates/electron number density (n e ). These authors found rate coefficents for photoionization between 10 −9 to 10 −15 cm 3 s −1 depending on the electron temperature and density [10]. Other photoionization rates have been reported [11], but these rates describe multi-photon ionization during the formation of LPPs and thus are not applicable to the CR model considered here.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Colombant and Tonan [5] used units of cm 3 s −1 for rate coefficients for the three dominant processes and to express photoionization rates in these units Su et al considered rates/electron number density (n e ). These authors found rate coefficents for photoionization between 10 −9 to 10 −15 cm 3 s −1 depending on the electron temperature and density [10]. Other photoionization rates have been reported [11], but these rates describe multi-photon ionization during the formation of LPPs and thus are not applicable to the CR model considered here.…”
Section: Introductionmentioning
confidence: 83%
“…This minimum laser flux can be achieved easily with typical Nd:YAG lasers, with laser pulse energies, pulse widths, and focal spot diameters on the order of 1 J, 10 ns, and 100 µm, respectively. Where spot sizes are on the order of 10s of µm the minimum laser flux is greatly exceeded [6,[8][9][10]. Similarly, with T e = 3 eV and λ = 10.6 µm, a laser flux on the order of 10 7 W/cm 2 is found, which can be exceeded by laser energies, pulse widths, and focal spot diameters on the order of 1 J, 1 µs, and a few mm, respectively.…”
Section: Limits Of Applicabilitymentioning
confidence: 95%
See 3 more Smart Citations